Perceived Barriers and Facilitators to Implementation of Maternal and Child Health Care by Community Health Workers in Rwanda: A Qualitative Study - Hezagira Emery; Habineza Alphonse; Uwimana Lucie; Rutayisire Erigene (Journal of Public Health International, 2022)
The motivations and barriers experienced by community health workers (CHWs) during the delivery of maternal and child health (MCH) services are less documented in Rwanda. This study aimed to explore the barriers and facilitators of implementing MCH care as perceived by CHWs. A descriptive qualitative study was conducted, and Semi-structured interviews with flow-up probing questions were used to collect data. A number of 24 interviews were conducted with CHWs from three selected sectors of the Gicumbi district including four supervisors of CHWs from each selected health center and one at the district hospital. Three focus group discussions with CHWs from each site were also conducted. Ethical approval was obtained from Mount Kenya University and permission to collect data from the study sites was granted. NVIVO software was used for analysis, and then the content analysis was adopted to identify themes merging from the interviews and focus group discussions. The study findings revealed emerged factors that facilitate the CHWs to deliver MCH services to their communities: liking their work, trust by the community, respect from the community, the willingness to help, desire to gain knowledge, being human, and sacrifice for the wellness of the community. On another hand, the findings indicated that the work of CHW has various barriers including working many hours, lack of equipment, lack of knowledge, unsatisfactory salary, heavy workload, lack of working space, lack of facilitation for communication, family conflicts, lack of specified working time, and believes.
Keywords: Barriers